Perbedaan Kebersihan Rongga Mulut dan Kesehatan Periodontal Antara Mahasiswa Kedokteran Gigi dengan Mahasiswa Kesehatan Non-Kedokteran Gigi di Universitas Jember - Sita Amelia; Depi Praharani; Dyah Setyorini (Fakultas Kedokteran Gigi Universitas Jember, 2021)
Oral health is an important part of general body health and is related by several factors, behavioral domain factor is one of related factor consisting of knowledge, attitudes, and actions. The purpose of this study is to analyze the differences of oral hygiene and periodontal health in dental students with non-dental health students at Jember University. This research was an observational analytic with cross-sectional findings. The subjects were 274 Jember University health students. Data obtained by taking questionnaires and clinical examinations using OHI-S to determine the oral hygiene status and CPITN to examine the periodontal health status. The result of this study is dental students and non-dental health students has the same level of oral hygiene that is the medium level with lower OHI-S scores for dental students compared to non-dental health students. The conclusion of this study is there is no difference in the periodontal health status of dental students with non-dental health students at Jember University.